Rising moon of thoughts : dialogue between man and God = "Vicharcandrodaya": an ancient Sanskrit text - Pītāmbara, Dr., 1876 or 7- (Pankaj Publications ; distributors, Cambridge Book & Stationary [sic] Stores, 1982)
Treatise on the basic tenets of the Vedanta philosophy.